Training Tourism Business Budgeting for MSME Actors in Pematang Johar to Improve Operational Effeciency - Susan Grace Nainggolan; Junika Napitupulu; Widalicin Januarty; Muhammad Haris Riyaldi; Sipnarong Kanchawongpaisan; Muhammad Hafiz Abd. Rashid; Putri Handayani (Eastasouth Journal of Effective Community Services, 2025)
Budgeting training for tourism MSME entrepreneurs in Pematang Johar aims to improve their operational cost management and business efficiency. This activity involved 20 MSME entrepreneurs from the culinary, handicraft, and tourism service sectors. The training methods included lectures, discussions, case studies, and budgeting practice. The training results showed an increase in participants' understanding of budgeting concepts, their ability to prepare financial plans, and their awareness of controlling operational costs. Post-training monitoring showed a reduction in cost waste, prioritization of expenditures, and the use of cost-effective promotions. Thus, this training contributed to improving the efficiency and sustainability of tourism MSMEs in Pematang Johar.